PENGARUH SUBTITUSI TEPUNG LABU KUNING (CUCURBITA MOSCHATA) DAN IKAN LEMURU (SARDINELA LEMURU) TERHADAP SIFAT ORGANOLEPTIK ROTI MANIS LEMBUNING - Meirina Sulastri Loaloka; A.A Ayu Mirah Adi; Asweros Umbu Zogara (Universitas Citra Bangsa, 2020)
ABSTRACT Background. One effort to solve nutritional problems in NTT is to modify local food into nutritious food for children to consume. Local food ingredients used include lemuru fish and pumpkin. Lemuru and pumpkin contains protein, carbohydrates and antioxidants. Both of the two can be found in NTT and are easily available and inexpensive. Aim. To know the effect of the pumpkin flour substitution (Cucurbita Moschata) and lemuru fish flour (Sardinella Lemuru) on the organoleptic of Lembuning Sweet Bread. Methods. The type of research is an experiment, using a Completely Randomized Design that was tested using an organoleptic test with panelists taken from lecturers, staff, and students of Program Studi Gizi Poltekkes Kemenkes Kupang totaled 71 people, then analyzed using the ANOVA test. This research was conducted in June to July 2018 in the Food Technology Laboratory of Program Studi Gizi Poltekkes Kemenkes Kupang. Results. There was no effect on the quality of pumpkin substitute sweet bread and lemuru fish based on indicators of color, taste, and aroma, while there was an influence on quality of pumpkin substitute sweet bread and lemuru fish based on texture. Conclusion. Sweet bread made from pumpkin flour substitution and lemuru fish need to be modified so that it is liked by children Keywords: lemuru fish, pumpkin, lembuning sweet bread